2015
DOI: 10.1016/j.envpol.2015.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the dispersion and transport of reactive pollutants in a deep urban street canyon: Using large-eddy simulation

Abstract: This study investigates the dispersion and transport of reactive pollutants in a deep urban street canyon with an aspect ratio of 2 under neutral meteorological conditions using large-eddy simulation. The spatial variation of pollutants is significant due to the existence of two unsteady vortices. The deviation of species abundance from chemical equilibrium for the upper vortex is greater than that for the lower vortex. The interplay of dynamics and chemistry is investigated using two metrics: the photostation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
90
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(92 citation statements)
references
References 32 publications
1
90
0
1
Order By: Relevance
“…As is customary in dispersion models at the local scale [75], reactions (3) and (4) are neglected, and the modelling of chemical transformation of nitrogen oxide relies on Equation (2) only. Since the radical O…”
Section: Modelling Chemical Reactionsmentioning
confidence: 99%
“…As is customary in dispersion models at the local scale [75], reactions (3) and (4) are neglected, and the modelling of chemical transformation of nitrogen oxide relies on Equation (2) only. Since the radical O…”
Section: Modelling Chemical Reactionsmentioning
confidence: 99%
“…where D is the molecular diffusion coefficient and Sc t is the turbulent Schmidt number. The value of Sc t is taken equal to 0.7, in accordance with previous atmospheric dispersion studies [56,57], while D is equal to 1.64•10 −5 m 2 •s −1 , which is the molecular diffusion coefficient for CO 2 at 25 • C [58], as a typical pollutant. For the implementation of this set-up, the coupling of pressure and velocity is solved by the Pressure-Implicit with Splitting of Operators (PISO) algorithm [59].…”
Section: Simulation Set-upmentioning
confidence: 99%
“…At the top of the domain, the symmetry boundary condition (symmetryPlane in OpenFOAM) was set, following the common practice for the quasi-2D set-up, e.g., [37,56,63]. This means that the normal velocity on this patch is assigned to zero and for the scalars there is a zero-normal gradient.…”
Section: Simulation Set-upmentioning
confidence: 99%
“…In a deep street canyon of H/W ¼ 5.7 with a traffic volume of smaller than 6000 vehicles from 0800 to 2100 LT, the road-to-roof CO concentration ratio is 2.6 from 0000 to 2400 LT and 3.5 from 0700 to 2100 LT, indicating the importance of on-road emission amount from vehicles (Murena and Favale, 2007). In a two-dimensional street canyon of H/W ¼ 2, computational fluid dynamics modeling studies have shown that a lower-to-upper concentration ratio is a function of emission rate (Kwak et al, 2013) and exchange velocity (Zhong et al, 2015).…”
Section: Introductionmentioning
confidence: 97%